Financial Distress in Manufacturing Companies: The Effects of Profitability, Liquidity, and Leverage Ratios with Audit Committee Moderation - DIVA AYU IMANDA SARI SARI (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
This study aims to provide empirical evidence on factors influencing financial distress in Indonesian manufacturing companies. Financial distress occurs when operating cash flow is insufficient to cover short-term liabilities, such as trade payables and interest expenses. The independent variables are profitability, liquidity, and leverage, with the audit committee as a moderating variable. From 181 companies listed on the IDX, 104 were selected through purposive sampling over a four-year period. Using descriptive statistics and logistic regression, the results show that profitability and liquidity have a negative and significant effect on financial distress, while leverage shows no significant effect. The audit committee does not moderate the relationships between these variables and financial distress.